Illicit drug use in the UK - MacDonald, Ziggy (The British journal of criminology, 1999)
The control of psychoactive substances presents a serious concern for policy makers who must take into account the allocation of scarce public resources resulting from their interventions. Much of the debate in this respect is carried out within an informational vacuum. This paper presents an analysis of the survey data currently available to policy makers. We consider the British Crime Survey (BCS) which is the primary source of UK drug use information and observe serious limitations to what it can provide. We find that it does not allow us to effectively analyse the problem of escalating drug use, nor can we identify the point of initiation into the drugs market or the duration of use. We recommend that some of these observational problems could be overcome if the BCS drug questions were presented in the reverse order. However, based on the three drug use questions currently presented in the BCS, we offer an analysis of past and present drug use in terms of socio-economic factors that are associated with use at the extensive margin